Contextualization of Amthal Verses in Quranic Malay Translation - Muhammad Arif Musa; Siti Khadijah Ahmad Tajuddin; Adnan Mohamed Yusoff; Ahmad Sanusi Azmi (Human Resource Management Academic Research Societ, 2024)
Indexed by ERA